Considerations on prediction horizon and dissipative losses for wave energy converters. Issue 14 (27th September 2021) - Shahroozi, Zahra; Göteman, Malin; Engström, Jens; Todalshaug, Jørgen Hals
Abstract: The non‐causal optimal control law for wave energy converters leads to a requirement of predicting waves and wave forces over a future horizon. Using examples of generic body shapes and oscillation modes, the authors show through computations of the velocity reference trajectory how the length of prediction horizon required to reach the maximum power output depends on the level of dissipative losses in the conversion chain . The sensitivity to noise is discussed, and so is the use of filtering to improve performance when the available prediction horizon is short or predictions are inaccurate . Considerations are also made for amplitude constraints and other effects encountered in a real system. With realistic assumptions for the level of dissipative losses, results indicate that the prediction horizon needed to approach the maximum achievable power output for real systems ranges from only a few seconds up to about half a wave period, which is shorter than that has generally been assumed earlier.